Conjunctivites in young animals of large livestock: the determination of microbial view and sensitivity to the antibacterial preparations - Мельничук, В. В. (Scientific Progress & Innovations, 2012)
In the article the data of the bacteriological studies of microflora of the conjunctival bag of calves with the signs of the doublesided inflammation of the connecting shell of the eyes of different nature in the age of 2-4 months are illuminated. The determinations of the sensitivity of the chosen microorganisms to the basic antibiotics is carried out in vitro, the antibacterial properties of the substances which are proposed for th e treatment, related to the revealed microorganisms are selected and studied.